Cellular and Molecular Pathophysiology of Traumatic Brain Injury: What Have We Learned So Far? - Marco Aurelio M. Freire; Gabriel Sousa Rocha; Leonardo Oliveira Bittencourt; Daniel Falcao; Rafael Rodrigues Lima; Jose Rodolfo Lopes P. Cavalcanti (Biology, 2023)
Traumatic brain injury (TBI) is one of the leading causes of long-lasting morbidity and mortality worldwide, being a devastating condition related to the impairment of the nervous system after an external traumatic event resulting in transitory or permanent functional disability, with a significant burden to the healthcare system. Harmful events underlying TBI can be classified into two sequential stages, primary and secondary, which are both associated with breakdown of the tissue homeostasis due to impairment of the blood–brain barrier, osmotic imbalance, inflammatory processes, oxidative stress, excitotoxicity, and apoptotic cell death, ultimately resulting in a loss of tissue functionality. The present study provides an updated review concerning the roles of brain edema, inflammation, excitotoxicity, and oxidative stress on brain changes resulting from a TBI. The proper characterization of the phenomena resulting from TBI can contribute to the improvement of care, rehabilitation and quality of life of the affected people.